Manajemen Strategi Peningkatan Mutu Pendidikan di SD Islam An-Nur Kota Serang Banten - Dedy Yansyah; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Departement of Mathematics Education, 2024)
This exploration intends to portray the Administration Methodology for Working on the Nature of Sekolah Training. The examination strategy utilized is a subjective illustrative technique. Information assortment procedures were helped out through meetings, perception and documentation studies. The consequences of the exploration show that the execution of Technique The board at SD Islam An Nur Kota Serang Banten Regime was brought out through: a drafting group comprising of the madrasa head, delegate head, 2 instructors and a madrasa council. The plan of the vision and mission is arranged utilizing short and clear sentences so realizing the normal benchmarks is simple. Examination of ecological open doors and dangers is examined in inward discussions as a reason for deciding strategy, yet has not been arranged in composed records. Long haul plans are ready for the initial 4 years, while yearly plans are ready in a deliberate way toward the start of every year. Expanding compelling, precise and productive learning keeps on being done by opening Bilingual classes directed by proficient staff from LBB English Town